Highly controlled vascular syringes for pericardiocentesis - Ricciardi, Mark; Roldan, Carlos; Sibbitt, Randy; Sibbitt, Jr, Wilmer; Michael, Adrian; Palmer, Dennis (The Journal of invasive cardiology, 2010)
The present study determined the utility and needle control characteristics of highly controlled vascular syringes for image-guided pericardiocentesis. Vascular syringes have been integrated into invasive cardiovascular procedures with improved patient safety, but to date have not been used in pericardiocentesis. To address this issue, we determined the method of use of vascular syringes for pericardiocentesis. A vascular syringe with reciprocating plungers, the reciprocating procedure device (RPD syringe), replaced the corresponding 10 ml and 20 ml conventional syringes in a standard pericardiocentesis tray. The vascular syringe is controlled with one hand, and can either aspirate or inject by pushing the corresponding aspiration or injection plunger. Four hundred and thirty seven subjects underwent vascular syringe procedures. The linear displacement method was used to precisely measure control of the needle tip in millimeters (mm) in vascular syringes compared to conventional syringes in 20 individual operators. Relative to the corresponding 10 ml and 20 ml conventional syringes, vascular syringes significantly reduced unintended forward penetration of the needle tip by 44% (7.0 ± 4.3 mm; p < 0.0001) and 53% (10.1 ± 5.5 mm; p < 0.0001), respectively, and reduced unintended retraction of the needle by 56% (2.7 ± 2.2 mm; p < 0.001) and 60% (3.5 ± 2.5 mm; p < 0.001), respectively. During pericardiocentesis, the mechanical syringe permitted facile one-handed aspiration and maintained the operator's ability to clear the needle. In the 437 vascular syringe procedures, there were no complications, with an estimated cost savings of $10-65 per procedure. Vascular syringes improve needle control in pericardiocentesis, promote patient safety and permit one-handed aspiration and injection.